Pharmacokinetics and pharmacodynamics of medication in asphyxiated newborns during controlled hypothermia. The PharmaCool multicenter study - de Haan, Timo R (BioMed Central, 2012)
BACKGROUND: In the Netherlands, perinatal asphyxia (severe perinatal oxygen shortage) necessitating newborn resuscitation occurs in at least 200 of the 180–185.000 newly born infants per year. International randomized controlled trials have demonstrated an improved neurological outcome with therapeutic hypothermia. During hypothermia neonates receive sedative, analgesic, anti-epileptic and antibiotic drugs. So far little information is available how the pharmacokinetics (PK) and pharmacodynamics (PD) of these drugs are influenced by post resuscitation multi organ failure and the metabolic effects of the cooling treatment itself. As a result, evidence based dosing guidelines are lacking. This multicenter observational cohort study was designed to answer the question how hypothermia influences the distribution, metabolism and elimination of commonly used drugs in neonatal intensive care. METHODS/DESIGN: Multicenter cohort study. All term neonates treated with hypothermia for Hypoxic Ischemic Encephalopathy (HIE) resulting from perinatal asphyxia in all ten Dutch Neonatal Intensive Care Units (NICUs) will be eligible for this study. During hypothermia and rewarming blood samples will be taken from indwelling catheters to investigate blood concentrations of several antibiotics, analgesics, sedatives and anti-epileptic drugs. For each individual drug the population PK will be characterized using Nonlinear Mixed Effects Modelling (NONMEM). It will be investigated how clearance and volume of distribution are influenced by hypothermia also taking maturation of neonate into account. Similarly, integrated PK-PD models will be developed relating the time course of drug concentration to pharmacodynamic parameters such as successful seizure treatment; pain assessment and infection clearance. DISCUSSION: On basis of the derived population PK-PD models dosing guidelines will be developed for the application of drugs during neonatal hypothermia treatment. The results of this study will lead to an evidence based drug treatment of hypothermic neonatal patients. Results will be published in a national web based evidence based paediatric formulary, peer reviewed journals and international paediatric drug references. TRIAL REGISTRATION: NTR2529.